Effectiveness of Canine Hip Dysplasia and Elbow Dysplasia Improvement Programs in Six UK Pedigree Breeds - James, H. K.; McDonnell, F.; Lewis, Thomas W. (Frontiers in Veterinary Science, 2020)
Hip and elbow dysplasia are common disorders in larger dog breeds and crosses, and a known contributory factor to osteoarthritis, lameness and reduced mobility. Screening schemes evaluating the severity of hip and elbow dysplasia in the UK are administered by the British Veterinary Association (BVA) and the Kennel Club (KC). The BVA/KC Hip Dysplasia scoring scheme is over 50 years old, having originated in 1965, and has operated in its current form since 1983. The BVA/KC Elbow Dysplasia grading scheme commenced more recently in 1998 and is based on the International Elbow Working Group guidelines. Hip score and elbow grade data on a considerable number of dogs in the UK have been generated from these two screening schemes. This study analyses data from dogs of six breeds scored from 1990 to present, to establish any determinable trends in hip score and elbow grade parameters, and to examine whether the implementation of such schemes has had a positive influence on hip and elbow health. A range of criteria, including the rate of participation in the screening schemes, hip score and elbow grade parameters (e.g. median, mean, standard deviation), and estimated breeding values (EBVs) were analysed, both in the overall population and also among breeding animals. The results show a general decline in hip score parameters (median, mean, standard deviation and 75th percentile), revealing a reduction in the prevalence and severity of hip dysplasia. There was a more modest decline in mean elbow grade within breeds. The proportion of sires and dams (of dogs born per year) with no hip score or elbow grade fell substantially over time, demonstrating good participation in the screening schemes. In most breeds, the scores of sires and dams are demonstrably improving. There is a declining genetic trend as ascertained by EBVs for both hip scores and elbow grades in most breeds, implying that the improvement observed is due in part to selection for improvement in hip and elbow health as described by the respective screening schemes.